Growing up in Ethnic Enclaves: Language Proficiency and Educational Attainment of Immigrant Children - Alexander M. Danzer; Carsten Feuerbaum; Marc Piopiunik; Ludger Wößmann (Center for Economic Studies and ifo Institute (CESifo), 2018)
Does a high regional concentration of immigrants of the same ethnicity affect immigrant children's acquisition of host-country language skills and educational attainment? We exploit the exogenous placement of guest workers from five ethnicities across German regions during the 1960s and 1970s in a model with region and ethnicity fixed effects. Our results indicate that exposure to a higher own-ethnic concentration impairs immigrant children's host-country language proficiency and increases school dropout. A key mediating factor for this effect is parents' lower speaking proficiency in the host-country language, whereas inter-ethnic contacts with natives and economic conditions do not play a role.
Keywords: J15; I20; R23; J61; 330; immigrant children; ethnic concentration; language; education; guest workers